Bond Premium Cyclicality and Liquidity Traps - Nicolas Caramp; Sanjay R. Singh (University of California, Department of Economics, 2020)
Safe asset shortages can expose the economy to liquidity traps. The nature of these traps is determined by the cyclicality of the bond premium. Self-fulfilling liquidity traps are associated with a counter-cyclical bond premium. Small issuances of government debt crowd out private debt and exacerbate these pessimism-driven recessions. In contrast, fundamental liquidity traps arise under a pro-cyclical bond premium and government debt is expansionary. In the data, we find evidence of a counter-cyclical bond premium and a pro-cyclical supply of safe assets. We propose robust policies that prevent the existence of self-fulfilling traps and are expansionary in fundamental traps.
Keywords: E0; E1; E5; E32; E52; 330; bond premium; safe assets; liquidity trap